Pembinaan Kompetisi Sains Madrasah Bidang Matematika Terintegrasi Untuk Meningkatkan Kompetensi Siswa - Pratama, Rian Ade; Ruslau, Maria Fransina Veronica (STKIP Andi Matappa, 2021)
The organization of the Madrasah Science Competition Coaching aims to improve students' competence in the field of integrated mathematics. The coaching takes place in three phases: firstly, planning, secondly, implementation and thirdly, evaluation. In the planning phase, the creation of books and questions is the first strategic step. The reference to the characteristics of the questions of the previous year becomes a material for the development and solution of questions. The implementation phase consists of selection, socialization, discussion, question and answer and coaching. The evaluation phase is divided into the evaluation of the student's competencies and the evaluation of the implementation of coaching. The assessment of the student competence is carried out by the Tryout 2 competition for integrated mathematics in the madrasah. The results of the coaching of the integrated math-madrasah-science competition at Madrasah Aliyah Al Munawarah Merauke have a good influence on the competence skills of the students. Coaching becomes an incentive program for students to participate in the 2020 Madrasa Science Contryout. During the entire coaching process, the students are active in questions, answers and discussions. The integrated mathematics assessment in experiment 1 to experiment 2 shows that the student's competence has increased. Meanwhile, the Tryout 2 results of the coaching participants have shown positive results to participate in the Madrasah Science Integrated Math Competency in 2020.